Effects of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) on cardiopulmonary function, body composition, and physical function in cancer survivors: a meta-analysis of randomized controlled trials - Peng, Chenggen; Hu, Ming; Yang, Linlin; Yuan, Zhichao (Frontiers in Physiology, 2025)
BackgroundAdvances in cancer treatment have led to a significant increase in the global number of cancer survivors. However, long-term health management challenges—such as reduced cardiopulmonary function, cancer-related fatigue, and metabolic dysregulation—remain formidable. The purpose of this study was to conduct a meta-analysis of randomized controlled trials (RCTs) to comprehensively compare the effects of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) on Cardiopulmonary function, body composition, and physical function in cancer survivors. Thereby providing evidence-based guidance for individualized exercise prescriptions.MethodsBy the PRISMA guidelines, we systematically searched databases including PubMed, Web of Science, Scopus, Embase, the Cochrane Library, and EBSCOhost up to February 2025. A total of 12 eligible RCTs were included, breast cancer (n = 7), colorectal cancer (n = 3), and mixed cancer types (n = 2). Meta-analysis was performed using Cochrane Collaboration’s Review Manager 5.4, while sensitivity analyses were conducted with Stata MP 14.0 to assess the stability and reliability of the results. Egger’s test was utilized to evaluate the presence of publication bias.ResultsThe meta-analysis revealed that, compared with MICT, HIIT was significantly more effective in improving VO2 peak (Peak Oxygen Uptake) in cancer survivors [SMD = 0.53, 95% CI (0.21, 0.84), Z = 3.30, P = 0.001]. However, no statistically significant differences were found between HIIT and MICT in terms of body composition (including Body Mass, Total Fat Mass, Lean Body Mass, Fat Percentage, Body Mass Index, Waist Circumference, and Hip Circumference) or physical function (including Sit-to-Stand Test and 6-Minute Walk Test).ConclusionHIIT appears superior to MICT in enhancing VO2 peak and, consequently, cardiopulmonary function in cancer survivors. Nonetheless, both training modalities yield comparable outcomes in body composition and physical function. Given the variability in the quantity and quality of the included studies, further well-designed and objective RCTs are warranted to validate these findings.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD420250654968.